Increasing the Brand Awareness of Sosis Solo Nyonya Veronica by Finding a New Market Segment and Creating the Packaging of the Frozen Food - Rafael Juan Santoso; Jusuf Imam Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2024)
The writer selected Sosis Solo Nyonya Veronica for this article. Sosis Solo Nyonya Veronica is a small business in the food sector. The brand was founded in 2022, and the main product is Sosis Solo. The problem of this business is low brand awareness. Its market is limited to warung soto customers in Solo because their ready-to-eat products go bad easily. To increase the brand awareness and sales, this business must sell the frozen food variant to customers from other cities. This is where a good packaging matters. In the research, the writer collected the data from the customers and the target market to know the level of the brand awareness and their opinions regarding frozen food and packaging. From the 50 respondents, the writer found out that the brand awareness level is low, belonging only to level 1 or No Recognition (46%) and level 2 or Brand Recognition (54%). The respondents confirmed that packaging for the frozen food is Very Important (54%) and Important (42%). They also said the packaging should contain the logo, brand name, and WhatsApp number. By selling the frozen food variants to another market (food stores), the brand awareness Sosis Solo Nyonya Veronica will expand to other cities and the sales will in turn increase.